ENERGIA AMIGA: PROTEÇÃO CONTRA DESCARGAS ATMOSFÉRICAS SEGUNDO A NBR 5419 - Jablonski, Rodrigo Schettert; Pereira, Ubiratan De Oliveira; Commandeur, Caroline Denardi; Moraski, Mateus Eichkoff; Radüns, Caroline Daiane Radüns; Schultz, Fernando Da Cruz (Salão do Conhecimento, 2018)
Projeto de Extensão – Energia Amiga